Improving Work Regulations and Administrative Arrangements at “KSP Mitra Mandiri Abadi” - Ninda Putri Kusumawardhani; Audita Nuvriasari (PT FORMOSA CENDEKIA GLOBAL, 2023)
Savings and Loans Cooperatives or in Indonesian called “Koperasi Simpan Pinjam (KSP)” are business entities whose management requires work regulations and good administrative arrangements so that they can run well. The purpose of this program is to improve the work skills of administrative staff at KSP Mitra Mandiri Abadi and increase employee awareness in complying with the work regulations. The method used is the transfer of knowledge and technology through work practices and socialisation activities. The result of the activity is the frequency of employee attendance running efficiently and regularly and improving the quality of discipline in the management of KSP Mitra Mandiri Abadi.